Metaphors We Die By - Jezhny, Karzan A. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study which is entitled “Metaphors We Die By” is concerned with death metaphor in Central Kurdish. The expression “we” in the title refers to Kurdish people, i.e. the study is a detailed explanation of metaphors the Kurds die by. It attempts to elucidate how Central Kurdish speakers think about death. In other words, the main aim of the study is to identify the perspective of Central Kurdish (CK) speakers on the phenomenon of death. The primary questions of the study are: Ho do the Kurds contemplate death? What are the source conceptual domains that CK speakers rely upon to understand death? What factors paly a role in structuring the conceptual mappings of the linguistic metaphors? The study explicates the concept of death in CK from the standpoint of Conceptual Metaphor Theory (CMT). According to the Cognitive approach to metaphor, it explores the way Kurdish speakers think about death. The study is particularly significant for understanding Kurdish culture and their perspective on one of life’s most important phenomena. The interpretation of death according to the framework of CMT involves the identification of various source domains that play a role in the conceptualization of death. The data of the study is based on everyday speech of CK through which an attempt is made to infer Kurdish thoughts and worldviews about death. Hence, the study, in light of the theory it relies on, views language as a reflection of thought. In CMT, thought has a metaphorical nature, so language, which is a mirror of thought, basically operates metaphorically.